1987
DOI: 10.1002/pssa.2211000233
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of the refractive index of Hg1–xCdxTe

Abstract: The refractive index of the ternary compound Hg1–xCdxTe is measured over a large energy region for several alloy compositions x between x = 0.18 and 1.0 at room and liquid nitrogen temperatures. The experimental results are compared with two theoretical models and with the Sellmeir equation. The analytical expression describing the compositional dependence of the refractive index is derived by fitting the compositional dependence of Sellmeir coefficients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…10 We found that most expressions, such as the dielectric functions and the absorption coefficients, could be taken straight from the literature. [16][17][18][19][20][21] However, the model for the bandgap of MCT was more difficult to realize. Initially, we started with the Hansen, Schmidt, and Casselman (HSC) model, 22 but our experimental data showed this to be insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…10 We found that most expressions, such as the dielectric functions and the absorption coefficients, could be taken straight from the literature. [16][17][18][19][20][21] However, the model for the bandgap of MCT was more difficult to realize. Initially, we started with the Hansen, Schmidt, and Casselman (HSC) model, 22 but our experimental data showed this to be insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…Interference fringes in the transparent portion of the transmission spectra were Fourier transformed to obtain the average optical path length of the film. 4 Assuming an average index of refraction, 5 we can map the effective thickness of the film. Figure 1 shows the effect of annealing on the FWHM of the band-edge PL.…”
Section: Methodsmentioning
confidence: 99%
“…Constant values of the real part of refractive index η at 80K are not sufficient to accurately model the spectral response, around the cut-off wavenumber region. Figure 3 represents the superposition of modeled spectral responses using constant values of η, at 80K, found in Kucera's article, 10 for cadmium composition x = 0.292 (corresponding to MWIR region, operating conditions). According to the classical definition of cut-off wavenumbers, corresponding to the wavenumber at which the pixel response drops to 50\% of its peak value, 11 we notice an important difference of the cutoff wavenumbers σ cut-off .…”
Section: Relation Between the Cut-off Wavelength And The Refractive Imentioning
confidence: 99%
“…In the past few decades, optical absorption in HgCdTe has been widely investigated, 10,[13][14][15][16][17] as it is necessary to evaluate detectors performance, such as quantum efficiency, using semiconductor physics laws.…”
Section: Hgcdte Absorption Coefficientmentioning
confidence: 99%